2017
DOI: 10.1021/acs.joc.7b01813
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Utility of Arylmethylsulfones: Annulative π-Extension of Aromatics and Hetero-aromatics Involving Pd(0)-Catalyzed Heck Coupling Reactions

Abstract: A straightforward and general method for the synthesis of annulated thiophene, dibenzothiophene, and carbazoles analogues has been achieved involving alkylation of 2-bromo-1-(phenylsulfonylmethyl)arene/heteroarene with arylmethyl bromides/heteroarylmethyl bromides using t-BuOK as a base in DMF, followed by Pd(0)-mediated intramolecular Heck coupling in the presence of KCO in DMF at 80-140 °C. The attractive feature of this protocol is that a wide variety of π-conjugated heterocycles could be readily accessed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…When the annulation reaction was conducted at 110 °C for 4 h, the N-sulfonyl groups remained untouched, providing access to compound 388 (Scheme 86). 192 In a report disclosing preparation and studies of the photoluminescent behavior of an extensive set of fused carbazole derivatives, a single example of an indolo[2,3-c]carbazole, namely compound 389, was reported as a product from the indium-catalyzed cyclization of the 3,3′-biindolyl 390 with methyl propargyl ether (Scheme 87). 513 Following a virtual high-throughput screening toward new materials for OLED devices, the system 391 was identified as a promising candidate.…”
Section: Indolo[32-b]carbazole Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…When the annulation reaction was conducted at 110 °C for 4 h, the N-sulfonyl groups remained untouched, providing access to compound 388 (Scheme 86). 192 In a report disclosing preparation and studies of the photoluminescent behavior of an extensive set of fused carbazole derivatives, a single example of an indolo[2,3-c]carbazole, namely compound 389, was reported as a product from the indium-catalyzed cyclization of the 3,3′-biindolyl 390 with methyl propargyl ether (Scheme 87). 513 Following a virtual high-throughput screening toward new materials for OLED devices, the system 391 was identified as a promising candidate.…”
Section: Indolo[32-b]carbazole Polymersmentioning
confidence: 99%
“…Subsequent cyclization in the presence of catalytic amounts of palladium acetate and triphenylphosphine provided a new route to the parent indolo­[3,2- a ]­carbazole 2 (Scheme ). Although this preparative route is inferior compared to an old method for synthesis the unsubstituted system 2 due to the poor atom economy, it may nevertheless have potential in future synthetic applications aiming at, for instance, unsymmetrically substituted derivatives.…”
Section: Indolo[32-a]carbazolesmentioning
confidence: 99%
“…These long‐range correlations allowed assignment of damirine A ( 1 ) as an indolo[3,2‐ a ]carbazole fused to an aminoimidazole ring, whereas damirine B ( 2 ) had the same indolocarbazole core fused to an imidazolone moiety. Although the indolo[3,2‐ a ]carbazole scaffold has been generated in prior synthetic studies, [ 6,14 ] it has only rarely been found in a natural product. Damirines A ( 1 ) and B ( 2 ) provide new carbon–nitrogen skeletons not seen in any other reported secondary metabolites, and damirine A ( 1 ) exhibited selective growth inhibitory effects against six different cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The annulation of 2-bromomethylindole 9 (0.2 g, 0.48 mmol) with 1,3,5-tri(thiophen-2-yl)benzene (0.170 g, 0.53 mmol) using anhyd SnCl 4 (0.025 g, 0.096 mmol) adopting the general procedure, followed by workup and column chromatographic purification (silica gel, EtOAc/hexane 1:9) gave carbazole 10i as a colorless solid; yield: 0.182 g (63%); mp 128-130 °C. 4, 143.3, 139.5, 139.0, 137.7, 137.4, 136.6, 135.8, 135.4, 133.9, 129.1, 128.2, 128.1, 127.7, 126.5, 125.5 (2 C), 124.2, 124.0, 123.4, 123.0, 120.0, 119.7, 115.3, 114.2, 108 The domino reaction of 2-bromomethylindole 9 (0.20 g, 0.48 mmol) with thienocarbazole 11 17 (0.16 g, 0.52 mmol) using anhyd SnCl 4 (0.025 g, 0.096 mmol) in anhyd 1,2-DCE (10 mL) at rt for 2 h, followed by usual workup and column chromatographic purification (silica gel; EtOAc/hexane 3:97) furnished benzo [b]carbazole 10j as a colorless solid; yield: 0.177 g (63%); mp 144-148 °C.…”
Section: -[35-di(thiophen-2-yl)phenyl]-9-(phenylsulfonyl)-9h-thieno-[23-b]carbazole (10i)mentioning
confidence: 99%